A FMKL-GLD Quantile Method for Estimating Economic Growth in Nigeria in the Presence of Multicollinearity and Outlier (Statistics, Optimization & Information Computing, 2024)
Nigeria’s economic growth posed to be a serious concern to policymakers, economics and scholars due to the challenges of economic characteristics, consequences and contradictions. Despite the effort made by the Central Bank of Nigeria in implementing several policies such as tightening of monetary policy rate and heavy borrowing for infrastructural development to stimulate economic growth in the past few years. The economic growth in Nigeria between 1999-2007 was 6.95 percent, between 2008-2010, it was stood 7.98 percent and it was 4.80 percent between 2011-2015 and from 2016 till day the economic growth stood at 0.81 percent. In this study, we estimate parameters to determine Nigerian economic growth in the presence of multicollinearity and outliers. We employed the FMKL-GLD quantile model to quarterly data from 1986 to 2021 obtained from the Central Bank of Nigeria. Exploratory data analysis (EDA) and diagnostic test carried out ascertained the presence of multicollinearity and outlier. However, it was discovered that in model that  INDT, RINR, REXR and OPEN contributed positively to the economic growth to the turn of 0.15%, 0.24%, 0.06% and 1.76%  while, it was revealed that EXDT contributed negatively to the economic growth in Nigeria thus, reduced economic growth by 0.02% and as such showed the tendency and potential macroeconomic variables under study as a veritable determinant of economic growth. The location, scale and space parameters , , , and  for the fitted FMKL-GLD model were -0.0253, 34.1488 -0.3303, and -0.5758. Therefore, it can be concluded based on the location, scale and space parameters from FMKL-FGLD and GLD Q,Q plots as well as the estimated parameter of RGDP, FMKL-FGLD was the best model that described the economic situation in Nigeria by showing that economy was growing in retrogressive direction and the need for drastic effort and strong willed to curtail the situation. To achieve this, the adoption of economic openness to the development and the growth of economy in Nigeria is a veritable policy direction that must be strictly followed.